Dynamics of changes in the structure of the hippocampus in a myocardial dysfunction. - Rodinskij, O. G.; Kozlova, Ju. V. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. It is well known that cardiovascular disease lead to the disruption of integrative functions of the brain, provided by hippocampus. Objective. To investigate the dynamics of spatial and quantitative pathological changes of hippocampal neurons under experimental myocardial dysfunction. Methods. Brain of male Wistar rats were divided into experimental (injected with doxorubicin) and control (injected with 0.9% solution of NaCl) groups. Results. Brains of rats of the experimental group underwent significant pathological changes in glia, as well as vascular system. In the superficial layers cerebral cortex looked as porous, spongy mesh structure. The vessels of the brain at all levels have demonstrated the phenomena of circulatory disorders in the form of congestion and stasis. Analysis of cytoarchitectonics of the hippocampus of rats in the control group showed significant differences in the quantitative composition of neurons in field CA1, CA3 and dentate gyrus (50,3 ± 1,1; 66,6 ± 0,6 and 60,4 ± 1,1 in R≤ 0.05, respectively). Conclusion. In conditions of experimental myocardial dysfunction in the hippocampus a gradual loss of individual neurons, and rows of cells was revealed. The most sensitive areas of the hippocampus in those conditions was a field CA3, where the total loss of the cellular composition for a period of follow-up was 45.1%. Except quantitative changes of a qualitative change in the form of loss of order neurons, loosening of rows and a violation of the blood supply to the brain vessels was detected.